Question
upstudy study bank question image url

1.1 Prove that the sum of \( n \) terms of an arithmetic series is given by the following formula: 1.2 Given the arithmetic series \( 5+9+13+\ldots \) 1.2.1 Determine the sum of the first \( n \) terms of the series in terms of \( n \). Leave your answer in simplified form. 1.2.2 Calculate the value of the \( 29^{\text {th }} \) term of the series. 1.2 .3 Calculate the value of \( n \) if it is further given that the sum of the first \( n \) terms of the series is 2015 .

Ask by Fernandez Erickson. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

**1.1 Sum Formula:** The sum of the first \( n \) terms of an arithmetic series is \( S_n = 2n^2 + 3n \). **1.2.1 Sum of the First \( n \) Terms:** \( S_n = 2n^2 + 3n \) **1.2.2 29th Term:** \( a_{29} = 117 \) **1.2.3 Number of Terms for Sum 2015:** \( n = 31 \)

Solution

Sign in to Unlock Answers for Free!

A Learning Platform Trusted by Millions of Real Students and Teachers.

star-icon Unlock

Reviewed and approved by the UpStudy tutoring team

Mind Expander

The sum of the first \( n \) terms of an arithmetic series can be derived from the formula \( S_n = \frac{n}{2} (2a + (n-1)d) \), where \( a \) is the first term and \( d \) is the common difference. This formula is derived from adding the first term to the last term, the second term to the second-last term, and so on, demonstrating the beauty of symmetry in mathematics! For the series \( 5 + 9 + 13 + \ldots \), the first term \( a = 5 \) and the common difference \( d = 4 \). The sum of the first \( n \) terms becomes \( S_n = \frac{n}{2} (2 \cdot 5 + (n-1) \cdot 4) = \frac{n}{2} (10 + 4n - 4) = \frac{n(4n + 6)}{2} = 2n^2 + 3n \). Now, for the \( 29^{\text{th}} \) term, we use the nth-term formula \( a_n = a + (n-1)d = 5 + (29-1) \cdot 4 = 5 + 112 = 117 \). Lastly, to find \( n \) when the sum is 2015, we solve the equation \( 2n^2 + 3n = 2015 \). Rearranging gives us \( 2n^2 + 3n - 2015 = 0 \). Using the quadratic formula \( n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), we find \( n = \frac{-3 \pm \sqrt{3^2 - 4 \cdot 2 \cdot (-2015)}}{2 \cdot 2} = \frac{-3 \pm \sqrt{9 + 16120}}{4} = \frac{-3 \pm 127}{4} \). Thus, \( n = 31 \) is the positive solution.

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy